2013
DOI: 10.1007/s10865-013-9539-0
|View full text |Cite
|
Sign up to set email alerts
|

Who’s asking the important questions? Sexual topics discussed among young pregnant couples

Abstract: Purpose The aim was to examine gender differences in sexual risk communication among young couples and factors influencing communication. Methods Sample consisted of 296 young pregnant couples. We assessed individual, interpersonal, and community factors on sexual risk communication. The Actor-Partner Independence Model was used to assess actor and partner effects on sexual risk communication. Results For actor effects, being female, older, not being Hispanic, and higher condom use self-efficacy was associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Young men and women with more open sexual health communication have increased condom use [30,31] as well as more dual method use [31]. However, less than half of adolescents report any such communication with their dating partners [31], and young men report less communication regarding sexual topics than young women [32]. …”
Section: Young Men’s Sexual Health Communicationmentioning
confidence: 99%
“…Young men and women with more open sexual health communication have increased condom use [30,31] as well as more dual method use [31]. However, less than half of adolescents report any such communication with their dating partners [31], and young men report less communication regarding sexual topics than young women [32]. …”
Section: Young Men’s Sexual Health Communicationmentioning
confidence: 99%
“…Among an ethnically diverse sample of young couples in the United States, it was found that if the woman has sexual partners outside of their relationship this negatively affects SSC (Albritton et al, 2014). With regards to male partners, as opposed to facilitating SSC as it was recorded among Latino couples in this review (Ashburn et al, 2008), among cohabitating couples in Kenya, if the male had other sexual partners, the couple was less likely to have discussed HIV prevention (Chiao et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…However, the same tendency was not identified in previous research regarding sexual communication with family and perceived social support from significant others. Thus, social support from and sexual communication with family can play a pivotal role in heightening sexual communication efficacy with significant others later in life (Albritton et al, 2014). However, once individuals are away from home and build new relationships outside the family of origin, their core support system tends to shift to friends and/or one's partner rather than family (Lee et al, 2020).…”
Section: The Relationship Between Sexual Communication and Perceived ...mentioning
confidence: 99%
“…Sexual minorities who have family support are able to communicate with others and express their sexual identity more freely (Goldfried & Goldfried, 2001). Interestingly, family support also serves as a motivation to engage in sexual communication (Albritton et al, 2014). When the family environment is perceived as supportive, it positively reinforces parent-child sexual communication regardless of sexual identity (Booth-Butterfield & Sidelinger, 1998).…”
Section: Introductionmentioning
confidence: 99%